Upaya Meningkatkan Hasil Belajar Lay Up Shoot Bola Basket Melalui Media Youtube Tutorial Teman Sebaya Pada Siswa Smpn 5 Kota Bengkulu - A, Rahman; Mesterjon, Mesterjon; Perdima, Feby Elra (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
To determine the extent to which the learning outcomes of Lay Up Shoot basketball through Youtube media Peer tutorials on SMPN 5 Bengkulu City Students. This research design is a class action research with research procedures through; planning, action, observation, and reflection. The subjects of this research were students of class X A SMPN 5 Bengkulu City, totalling 36 students. The research instruments used were lay up shoot tests and observation sheets. The results showed that YouTube media peer tutorials were very effective in improving the learning outcomes of lay up shoots in basketball games at SMPN 5 Bengkulu City. The increase in learning outcomes of lay up shoot in basketball games using youtube media peer tutorials is with an average value of 70.27 in cycle I increasing to 80.55 in cycle II. 2) In addition to improving the quality of learning, the peer tutorial method is recommended to assist teachers in fostering excitement and fun in students in competitive situations and being able to motivate students in learning.